Exogenous polyamines enhance resistance to Alternaria alternata by modulating redox homeostasis in apricot fruit. (15th December 2019) - Li, Yongcai; Ma, Yueyue; Zhang, Tingting; Bi, Yang; Wang, Yi; Prusky, Dov
Highlights: Exogenous polyamines exhibited preventive effect against black spot of apricot fruit. The preventive effects depended on the type of polyamines and concentration level. Exogenous polyamines treatment regulated ROS metabolism in apricot fruit. Exogenous polyamines treatment maintained redox balance in apricot fruit. Abstract: The effects of exogenous polyamines treatment on reactive oxygen species (ROS) metabolism in apricot fruits were systematically analyzed through the investigation of their curative and preventive effects on black spot disease. Results showed that 1.5 mM spermine (Spm), 1.5 mM spermidine (Spd) and 10 mM putrescine (Put) treatment significantly inhibited black spot development, additionally, the efficacy of this control was dependent upon the type of polyamines used and concentration level applied. Further studies have shown that exogenous polyamines treatments significantly improved production of O2 − and H2 O2, and increased the activities and gene expression levels of NADPH oxidase (NOX), super oxide dismutase (SOD), catalase (CAT) ascorbate peroxidase (AXP) and glutathione reductase (GR) in apricot fruit. Increased ascorbic acid (AsA) and reduced glutathione (GSH) content were also observed after exogenous polyamines treatment. These results have revealed that postharvest polyamines treatment effectively enhanced disease resistance through the maintenance of homeostasis in apricot fruits.